Effect of different fertilizers on the bacterial community diversity in rhizosperic soil of broomcorn millet (Panicum miliaceum L.). Issue 5 (16th April 2022) - Cao, Xiaoning; Wang, Junjie; Liu, Sichen; Chen, Ling; Xiang, Dabing; Na, Xiaofan; Qiao, Zhijun
ABSTRACT: The bacterial community structure and diversity in the rhizosphere of broomcorn millet treated with different fertilizers were analyzed. The crops were grown under one of the four fertilization treatments: M1 (compound fertilizer), M2 (farmyard manure), M3 (biological bacterial fertilizer), and M4 (no fertilizer). The soil DNA was isolated, and the 16S rRNA library was sequenced using Illumina MiSeq sequencers. The bacterial diversity and the differential bacterial genera in four groups were analyzed. Compound fertilizers had the most significant effect on plant growth, followed by farmyard manure and then biological bacterial fertilizer (p < 0.05). Actinobacteria and Pseudomonas sp. were dominant in all soil samples. The abundance of Actinobacteria was higher in M1 and M4, and the abundance of Pseudomonas sp. was higher in M3 and M4. The number of bacterial genera (208) was the highest in M1. Eight bacterial genera with low abundance were common in M1 vs. M3 and M2 vs. M3. Four bacterial genera with high richness ( Phormidium sp., Cellulosimicrobium sp., Yaniella sp., and Cloacibacterium sp.) overlapped in M1 vs. M3 and in M2 vs. M3. Compound fertilizer was the most effective at encouraging broomcorn millet growth (plant height, stem diameter, panicle weight, grain weight, and yield).